Are there differences between those doctors who apply for a training post in Foundation Year 2 and those who take time out of the training pathway? A UK multicohort study. Issue 11 (24th November 2019) - Cleland, Jennifer; Prescott, Gordon; Walker, Kim; Johnston, Peter; Kumwenda, Ben
Abstract : Introduction: Knowledge about the career decisions of doctors in relation to specialty (residency) training is essential in terms of UK workforce planning. However, little is known about which doctors elect to progress directly from Foundation Year 2 (F2) into core/specialty/general practice training and those who instead opt for an alternative next career step. Objective: To identify if there were any individual differences between these two groups of doctors. Design: This was a longitudinal, cohort study of 'home' students who graduated from UK medical schools between 2010 and 2015 and completed the Foundation Programme (FP) between 2012 and 2017. We used the UK Medical Education Database (UKMED) to access linked data from different sources, including medical school performance, specialty training applications and career preferences. Multivariable regression analyses were used to predict the odds of taking time out of training based on various sociodemographic factors. Results: 18 380/38 905 (47.2%) of F2 doctors applied for, and accepted, a training post offer immediately after completing F2. The most common pattern for doctors taking time out of the training pathway after FP was to have a 1-year (7155: 38.8%) or a 2-year break (2605: 14.0%) from training. The odds of not proceeding directly into core or specialty training were higher for those who were male, white, entered medical school as (high) school leavers and whose parents were educated to degree level. Doctors from areas of low participation in higher education were significantly (0.001) more likely to proceed directly into core or specialty training. Conclusion: The results show that UK doctors from higher socioeconomic groups are less likely to choose to progress directly from the FP into specialty training. The data suggest that widening access and encouraging more socioeconomic diversity in our medical students may be helpful in terms of attracting F2s into core/specialty training posts.